2020
DOI: 10.7759/cureus.11548
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Salivary Cortisol Level With Severe Depression and Family History

Abstract: Salivary cortisol level is considered a prominent depression biomarker, as saliva induces less stress as compared to blood. The study was performed in the physiology department, Sheikh Zayed Medical Institute Lahore from April 2015 to December 2015. Sixty participants, including 14 (46.67%) males and 16 (53.33%) females, in each non-depressive and depressive group of over 17 years of age, were undertaken. The depression diagnostics were performed both outdoors and in clinics and confirmed with the standards of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…15 Contrary to the perception about physical health, the general attitude of the public towards depression and motherhood was somewhat careless with 51% of them disagreeing with regards to depression being an understandable reason behind abortion. The results could've been towards people agreeing to abort pregnancy if the woman's mental health is compromised as traumas can result in severe disabilities, physical and mental including depression and anxiety, 16 which could drastically decrease the standards of living for the child itself. However, public's mutual disagreement highlights their perception that a new being, the bundle of joy, can erase past traumas as concluded by the people interviewed regarding abortion.…”
Section: Discussionmentioning
confidence: 99%
“…15 Contrary to the perception about physical health, the general attitude of the public towards depression and motherhood was somewhat careless with 51% of them disagreeing with regards to depression being an understandable reason behind abortion. The results could've been towards people agreeing to abort pregnancy if the woman's mental health is compromised as traumas can result in severe disabilities, physical and mental including depression and anxiety, 16 which could drastically decrease the standards of living for the child itself. However, public's mutual disagreement highlights their perception that a new being, the bundle of joy, can erase past traumas as concluded by the people interviewed regarding abortion.…”
Section: Discussionmentioning
confidence: 99%
“…Group therapy was excluded. Only articles containing at least one objective biomarker measure commonly associated with stress were included, such as changes in hormone or protein levels, blood pressure, galvanic skin response, heart rate, electro-physiological signals, and neural activity (Bagheri & Power, 2020; Gordon & Mendes, 2021; Hek et al, 2013; Khan, 2020; Satti et al, 2021; Taelman et al, 2009). There were no restrictions on the population.…”
Section: Methodsmentioning
confidence: 99%
“…Recent clinical studies in the PubMed/MEDLINE and EMBASE/Ovid were referenced to examine potential gender differences in cortisol expression. The majority of the studies conducted on salivary samples ( Table 1 ) in the past 10 years discovered no significant correlation between cortisol levels and depression symptoms between gender [ 8 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. However, studies conducted specifically on younger subjects found that cortisol reactivity was higher in male children, particularly during a state of depression [ 50 , 51 , 52 , 53 , 54 ].…”
Section: Gender Differences Of Cortisol In Clinical Studiesmentioning
confidence: 99%